The Importance of Guided Play in Classrooms to Promote Children’s Executive Functions : the Importance of Guided Play in Classrooms to Promote Children’s Executive Functions - Hermida, María Julia; Seabra, Alessandra Gotuzo; Bayley, Stephen (Universidade Presbiteriana Mackenzie, 2024)
Executive functions (EFs) comprise some of the most important mental processes for human thinking. Together, they play an essential role in helping us to regulate our thoughts and actions to achieve our goals. According to key literature, EFs include working memory (holding and manipulating information in one’s mind), inhibitory control (resisting impulses, ignoring distractions and delaying gratification), and cognitive flexibility (switching between mental sets and seeing things from different perspectives) (Diamond, 2006; Miyake et al., 2000). All these processes are critical for academic achievement, as well as the emotion regulation needed for school adaptation and a host of valuable later-life outcomes (Moffett & Morrison, 2020; Moffitt et al., 2011).
Keywords: Ciencias Sociales; Psicología